FACIAL NERVE PARALYSIS AND INTUSSUSCEPTION AS CLINICAL PRESENTATIONS OF LYMPHOBLASTIC LYMPHOMA: A RARE PEDIATRIC CASE REPORT - Musdalipa Musdalipa; Nadirah Rasyid Ridha; Setia Budi Salekede; Hadia Angriani (International Journal of Health Science & Medical Research, 2023)
Lymphoblastic lymphoma (LBL) is a highly aggressive lymphoblast neoplasm due to the presence of clonal hematopoietic stem cell abnormalities of B or T cell origin. LBL represents 30% of pediatric non-Hodgkin's lymphomas. We report a 2-year-11-month-old boy with complaints of a lump in the abdomen and facial paralysis on the left side. weight loss of 3 kg in 3 months, frequent nausea and vomiting, and constipation. On physical examination, the face was not symmetrical on the left and right. palpable mass from the right iliac region to the left iliac, measuring 17.5 x 10 x 5 cm, immobile, rubbery consistency. There is lymphadenopathy right inguinal region et sinistra. Abdominal ultrasound without contrast showed ileocolic intussusception, with histopathological results showing malignant non-Hodgkin's lymphoma. The therapy given was chemotherapy according to the protocol for non-Hodgkin's lymphoma. Facial nerve paralysis and intussusception are rare clinical features of LBL. It is important to consider a differential diagnosis such as LBL in a patient with a lump accompanied by facial nerve paralysis and intussusception. Histopathological and immunohistochemical examination were needed.Keywords:  Lymphoblastic Lymphoma; Facial Nerve Paralysis; Intussusception